PENGARUH TOTAL HUTANG, MODAL KERJA, DAN PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN SUB SEKTOR BATU BARA TERDAFTAR DI BEI - Zahara, Ani; Zannati, Rachma (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This study aims to determine and analyze the effect of total debt, working capital, and sales on net income. The object of this study is a company listed on the Indonesia Stock Exchange in the 2013-2017 period. The data retrieval technique used in this study is the purpose sampling method, which is based on the specified criteria. Data analysis techniques using multiple linear regression analysis method with analysis software Eviews 8.0. The findings are: (1) F test (simultaneous) in this study shows that total debt, working capital, and sales have a significant effect on net income, (2) T (partial) test in this study shows that total debt and sales have no effect significant to net income, while working capital has a significant effect on firm value. Keywords: Total Debt, Working Capital, Sales, Net Income